533. Demographic and Prognostic Indicators in COVID-19 Patients with ESRD: A Single Center Retrospective Study. (31st December 2020) - Chan, Kok Hoe; Patel, Bhavik; Ajao, Susanne O; Ramahi, Amr; Szabela, Maria E; Slim, Jihad
Abstract: Background: The first reported case of COVID-19 in the United States was in January 2020 and has since become a pandemic spreading rapidly worldwide. There is limited data on the epidemiology and prognosis of COVID-19 in end stage renal disease (ESRD) patients on hemodialysis (HD). In this study we describe our experience with 39 such patients who contracted COVID-19 disease. Methods: We conducted a retrospective hospital cohort study on patients ≥ 18 years old with ESRD on HD and confirmed COVID-19, who were admitted to our hospital between 03/15/2020 and 05/25/2020. Study individuals were recruited if they had a well-defined clinical outcome (discharged alive or expired). Demographic, clinical and laboratory data were reviewed and retrieved. Descriptive analysis, univariate and multivariate logistic regression methods were employed to describe the demographic and to identify prognostic markers associated with mortality. Results: Out of the 427 confirmed COVID-19 hospitalized patients during the study period, 39 ESRD patients on HD were included in this study, 19 (49%) expired, and 20 (51%) were discharged alive. Demographic analysis was tabulated in Table 1. The non-parametric analysis showed a significant difference in ethnicity, history of COPD, need of mechanical ventilation, ferritin, LDH, lymphocyte-ferritin ratio (LFR), lymphocyte-CRP ratio (LCR) and AST/ALT ratio between survival and non-survival groups (Table 1, 2). Mechanical ventilation is independently associated with mortality in ESRD patients with COVID-19 (odds ratio [OR] 21.11; 95% confidence interval [CI], 3.00–238.9). In addition, low AST/ALT ratio has an odd of survival in this group of patients (OR 0.45; 95% CI, 0.19–0.88). Table 1: Demographic Analysis of all ESRD patients with COVID-19. (HTN – Hypertension, DM – Diabetes mellitus, CAD – Coronary artery disease, CHF – Congestive heart failure, COPD – Chronic obstructive pulmonary disease) Table 2: Non-parametric analysis of all prognostic markers. (WBC – White blood count, ANC - Absolute neutrophil count, ALC - Absolute lymphocyte count, MPV – mean platelet volume, CRP – C-reactive protein, LDH – Lactate dehydrogenase, LFR – Lymphocyte-ferritin ratio, LDR - Lymphocyte-D-dimer ratio, LCR – Lymphocyte-CRP ratio, LLR - Lymphocyte-LDH ratio, AST – Aspartate transferase, ALT – Alanine transferase, BNP – Brain natriuretic peptide, NLR – Neutrophil-lymphocyte ratio, PLR – Platelet-lymphocyte ratio) Conclusion: Our observation of COVID-19 disease in patients with ESRD on HD confirms that this population is at the highest risk for mortality from SARS-CoV-2 infection, and that a low AST/ALT ratio is independently associated with decreased mortality, while mechanical ventilation had an increased mortality. Larger prospective studies in this population may help us understand better those prognostic markers and suggest how to intervene in order to decrease this catastrophic rate of mortality Disclosures: Jihad Slim, MD, Abbvie (Speaker's Bureau)Gilead (Speaker's Bureau)Jansen (Speaker's Bureau)Merck (Speaker's Bureau)ViiV (Speaker's Bureau)